La questione della cittadinanza tra educazione e politica: riflessioni critiche e proposte costruttive per il dibattito pedagogico - Francesco Pigozzo; Daniela Martinelli (University of Bologna, 2020)
Citizenship education is a core topic of all transformative pedagogies. In this article, we build on the phenomenological and critical schools of pedagogical thought in order to highlight some key theoretical issues that remain unaddressed in both the academic discourse and in the educational practices and policies aimed at fostering a new paradigm of citizenship education that can really fit with the political needs of the twenty-first century globalised society. Even the Intercultural and GCE approaches, in fact, fail to highlight the need to develop a critical awareness of the contradictions and unsustainability of today institutional framework with regards to State sovereignty and the peoples' right to self-determination, two major obstacles to the birth of multiscale citizenship and democracy.